Women-led community institutions as a potential vehicle for the adoption of varieties and improved seed practices: an impact case from India - Hossain, Mosharaf; Nayak, Swati; Mohapatra, Subhasmita; Trivedi, Pooja; Waza, Showkat A. (CAB International, 2024)
Rice–wheat rotation is the principal cropping system in South Asian countries. Increasing productivity under this cropping system in Northern India is not only a policy priority but also an important component towards ensuring food and nutritional security for the major portion of the Indian population. The objective of enhanced productivity is being pursued through innovative extension models focusing on the adoption of modern varieties and community-led seed production. The present experimental study (a randomized control trial) was conducted in Uttar Pradesh (India) to evaluate the efficacy of community institutions [e.g., women self-help group (WSHG)] based seed interventions in promoting the adoption of improved varieties amongst farmers. Besides, the impact on the implementation of quality seed production practices, adoption of seed quality measures, and participation in capacity-building trainings were also evaluated. The findings infer that implementing seed scaling programs through community institutions leads to a significantly higher rate of technological adoption than that executed through non-collectivized ways. Besides, farmers from WSHGs have more tendency towards learning new technologies and participating in training programs about improved crop management practices. The study also explains that WSHG-based programs are not a contributory factor in advancing farm technologies that are already in practice, such as seed cleaning and germination tests. This validated model can be suitably replicated for accelerated dissemination of seed-related innovations.